DIALEKTIKA STRUKTUR DAN AGENSI: Kontestasi Makna Living Qur’an pada Santri dan Alumni PP. Ar-Riyadhoh Klaten - Durrotunavisah El Tsalitsah; Muhammad Ibadurrochman; Azibur Rahman (STAI AL-ANWAR SARANG, 2025)
Amid rapid socio-cultural change, the sustainability of Qur’anic memorization beyond pesantren walls remains a critical yet underexplored issue in Living Qur’an studies. This research aims to examine how structural systems shape memorization practices, how actors construct the meaning of Living Qur’an, and how structure–agency contestation emerges in post-pesantren contexts. Employing a qualitative phenomenological design, data were collected through in-depth interviews with students, alumni, and teachers, and analyzed using thematic coding and comparative matrix analysis to identify essential patterns. Findings reveal a direct relationship between institutional structure (scheduled muroja’ah, sima’an partnership, layered evaluation) and the stability of memorization practices within the pesantren. However, an indirect effect occurs when a strong structural dependency weakens self-regulation, resulting in diminished continuity after graduation. The rhetoric–practice gap further shows that “living” the Qur’an is frequently reduced to ritual preservation rather than ethical transformation. Implications highlight the need for transition-oriented pedagogy that gradually shifts external control toward autonomous agency without overstating rejected assumptions about structural rigidity. The study contributes theoretically by advancing an ecological-structurational framework, integrating Bourdieu’s habitus and Giddens’ structuration theory to reconceptualize Living Qur’an as a dynamic interaction between system and actor.